Blood purification therapy in patients with severe COVID-19 requiring veno-venous ECMO therapy: A retrospective study. Issue 7 (July 2022) - Akil, Ali; Ziegeler, Stephan; Rehers, Stephanie; Ernst, Erik Christian; Fischer, Stefan
Objective: Patients with severe manifestations of COVID-19 might exhibit characteristics of a sepsis-like syndrome that can progress to multiple organ failure and ultimately death. Underlying mechanism have been explored and suggest a profound dysregulation of the immune system associated with hyperinflammation, hemodynamic instability and respiratory failure. Besides standard intensive care treatment, approaches modulating the dysregulated immune response, such as CytoSorb hemoadsorption, have been used. However, data of ECMO-dependent patients in comparison to a control cohort remain scarce. Methods: Included were 26 critically ill COVID-19 patients requiring high-flow veno-venous extracorporeal membrane oxygenation (high-flow VV ECMO) therapy due to severe acute respiratory distress syndrome (ARDS), of whom 16 were additionally treated with an extracorporeal hemoadsorption device, and compared to a control group of 10 patients. Assessed were levels of inflammatory markers, vasopressor requirements, oxygenation parameters, as well as clinically relevant outcome variables. Data were prospectively recorded and retrospectively analyzed. Results: Treatment with the applied multimodal therapy approach resulted in a stabilization in hemodynamics, a control of the hyperinflammatory response as evidenced by a significant reduction in inflammatory mediators, as well as a marked improvement in lung function. No device related adverse events were observed while treatment appeared safe and feasible. Conclusion: Treatment of a critically ill COVID-19 ARDS patients with combined VV ECMO support and hemoadsorption therapy led to a rapid and sustained hemodynamic stabilization, a control of the uncontrolled inflammatory response and an improvement in oxygenation. Given these signals pointing toward a patient-oriented benefit of extracorporeal hemoadsorption therapy in those patients, future controlled, randomized studies should focus on the investigation of the appropriate timing and dosing of this promising treatment modality.